Molecular Dynamics and Neutron Scattering Studies of Potassium Chloride in Aqueous Solution - Mason, Philip E; Tavagnacco, Letizia; Saboungi, Marie-Louise; Hansen, Thomas; Fischer, Henry E; Neilson, George W; Ichiye, Toshiko; Brady, John W (The journal of physical chemistry. B, 2019)
Neutron diffraction with isotopic substitution (NDIS) experiments were done on both natural abundance potassium and isotopically labeled 41KCl heavy water solutions to characterize the solvent structuring around the potassium ion in water. Preliminary measurements suggested that the literature value for the coherent neutron scattering length (2.69 fm) for 41K was significantly in error. This value was remeasured using a neutron powder diffractometer and found to be 2.40 fm. This revision increases significantly the contrast between the natural abundance K and 41K by about 30% (from 1.0 to 1.3 fm). The experimentally determined structure factor of the potassium ion was then compared to that calculated from molecular dynamics (MD) simulations. Previous neutron scattering measurements of potassium gave a solvation number of 5.5 (see below). In this study, the NDIS and MD results are in good agreement and allowed us to derive a coordination number of 6.1 for water molecules and 0.8 for chloride ions around each K+ ion in 4 molal aqueous KCl solution.
Keywords: simulace molekulární dynamiky; chlorid draselný; Molecular Conformation; Potassium Chloride; Neutron Diffraction; roztoky; Water; Molecular Dynamics Simulation; molekulární konformace; neutronová difrakce; Solutions; voda